2022
DOI: 10.3389/fendo.2022.895186
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Spontaneous Neuronal Activity and Microvascular Density of the Optic Nerve Head in Active Thyroid-Associated Ophthalmopathy

Abstract: PurposeTo investigate changes in local spontaneous brain activity in patients with active thyroid-associated ophthalmopathy (TAO) and explore the relationship between such alterations and microvascular indices.MethodsThirty-six active TAO patients with active phase and 39 healthy controls (HCs) were enrolled in this study. All participants underwent resting-state functional magnetic resonance imaging (rs-fMRI), neuropsychological tests, and ophthalmological examinations. The rs-fMRI-based fractional low-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Compared with HCs, patients with active TAO demonstrated decreased fALFF in the right calcarine (Zhu et al, 2022) and decreased FC between hemispheric calcarine gyri (Qi et al, 2022;Wen et al, 2022). The microvascular density of the optic nerve head has been negatively correlated with fALFF in the right calcarine (Zhu et al, 2022). Patients with TAO and in the euthyroid status showed decreased fALFF in the bilateral calcarine (Chen et al, 2021d) and decreased VMHC in lingual gyri/ calcarine .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Compared with HCs, patients with active TAO demonstrated decreased fALFF in the right calcarine (Zhu et al, 2022) and decreased FC between hemispheric calcarine gyri (Qi et al, 2022;Wen et al, 2022). The microvascular density of the optic nerve head has been negatively correlated with fALFF in the right calcarine (Zhu et al, 2022). Patients with TAO and in the euthyroid status showed decreased fALFF in the bilateral calcarine (Chen et al, 2021d) and decreased VMHC in lingual gyri/ calcarine .…”
Section: Discussionmentioning
confidence: 87%
“…Dysfunction in the primary visual cortex is a common finding among various eye diseases such as glaucoma (Chen et al, 2022b), diabetic retinopathy , exotropia and amblyopia (Liang et al, 2016;, and optic neuropathy (Sujanthan et al, 2022). Compared with HCs, patients with active TAO demonstrated decreased fALFF in the right calcarine (Zhu et al, 2022) and decreased FC between hemispheric calcarine gyri (Qi et al, 2022;Wen et al, 2022). The microvascular density of the optic nerve head has been negatively correlated with fALFF in the right calcarine (Zhu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of radiomics for TED therapy response prediction could be further enhanced. Despite EOMs, other vital structures in the orbit, such as lacrimal gland (LG) [19], orbital fat (OF) [20], and optic nerve (ON) [21], also undergo distinct changes in the pathogenesis of TED. The predictive value of these structures has been confirmed in several imaging studies [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on structural neuroimaging have identified morphological and microstructural abnormalities associated with visual and cognitive deficits in TAO patients (Silkiss & Wade, 2016 ; Wu et al, 2020 ). Researches based on resting‐state functional magnetic resonance imaging (rs‐fMRI) revealed that TAO patients exhibited abnormal functional changes in several brain networks, primarily within the visual network (Chen, Wu, Chen, Zhou, Chen, Xu, Hu, & Wu, 2021 ; Chen, Wu, Chen, Zhou, Chen, Xu, Wu, & Hu, 2021 ; Zhu et al, 2022 ). However, the previous functional investigations mostly concentrated on the alterations of localized brain activity, especially using amplitude of low‐frequency fluctuation (ALFF), one of the most reproducible and reliable fMRI parameters (Zhi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%